2021
DOI: 10.1038/s41420-021-00647-1
|View full text |Cite
|
Sign up to set email alerts
|

tRNA-derived small RNAs: novel regulators of cancer hallmarks and targets of clinical application

Abstract: AbstracttRNAs are a group of conventional noncoding RNAs (ncRNAs) with critical roles in the biological synthesis of proteins. Recently, tRNA-derived small RNAs (tsRNAs) were found to have important biological functions in the development of human diseases including carcinomas, rather than just being considered pure degradation material. tsRNAs not only are abnormally expressed in the cancer tissues and serum of cancer patients, but also have been suggested to regulate various vital cancer hallmarks. On the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 97 publications
(117 reference statements)
0
18
0
Order By: Relevance
“…man diseases, such as cancer [95]. Since an increasing number of tRFs appear to be rancRN they might affect the rate of protein biosynthesis during tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…man diseases, such as cancer [95]. Since an increasing number of tRFs appear to be rancRN they might affect the rate of protein biosynthesis during tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of such regulators in human pathogens could provide new insights into drug resistance strategies adopted by prokaryotes and could contribute to the development of RNA-based therapies against microbial infections [ 22 , 94 ]. Moreover, recent findings demonstrated the implication of tRNA-derived fragments (tRFs) in human diseases, such as cancer [ 95 ]. Since an increasing number of tRFs appear to be rancRNAs, they might affect the rate of protein biosynthesis during tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, emerging evidence has suggested that tsRNAs play a critical role in regulating cancer hallmarks, modifying tumour microenvironment, and modulating drug resistance by involving multiple biological processes, such as inhibition of mRNA translation, promotion of ribosome biogenesis, and regulation of epigenetic processes ( 22 26 ). Moreover, these findings highlight that tsRNAs can potentially be considered as biomarkers for cancer diagnosis and prognosis ( 27 29 ).…”
Section: Introductionmentioning
confidence: 88%
“…The functions of tsRNAs have drawn broad attention across the scientific world concerning cancers. So far, numerous studies have demonstrated that tsRNAs have pivotal functions in regulating proliferation, apoptosis, and migration of cancer cells, modifying tumour microenvironment, and modulating cancer drug resistance ( 29 ). Moreover, recent clinical research has revealed that tsRNAs were commonly detected in the serum samples from tumour patients ( 82 ).…”
Section: Biological Processes Correlated With Tsrnasmentioning
confidence: 99%
“…The role of the TSEN proteins in these diseases may be directly linked to splicing defects, or they may be linked to other shared roles for tRNA fragments in other diseases, such as Alzheimer's, diabetes, and aging (Li et al, 2021; Wu et al, 2021; Z. Zhou, Sun, et al, 2021). It remains unclear why these diseases are tissue specific, but this draws parallels to other tissue‐specific diseases associated with RNA processing factors such as ribosomopathies, which arise from mutations or altered expression of proteins involved in ribosome maturation [reviewed in Farley‐Barnes et al (2019) and McCann and Baserga (2013)].…”
Section: Transfer Rna Splicing Defects and Human Diseasementioning
confidence: 99%